Pollen transcriptomic analysis provided insights into understanding the molecular mechanisms underlying grafting-induced improvement in potato fertility - Zhang, Xing; Bai, Lei; Li, Maoxing; Li, Youhan; Hu, Ronghai; Guo, Huachun (Frontiers in Plant Science, 2024)
Introduction: Heterologous grafting has been proven to be a valid approach to improve potato fertility, especially when grafting potatoes with other Solanaceae family plants. However, the mechanisms underlying grafting-induced improvement in potato fertility are still unknown. Methods: In this study, a poor-fertility potato cultivar “Qingshu No. 9” (Q9) was grafted with a tomato cultivar “Zhongyan988” (ZY988) to study the effects of heterologous grafting in the former. The tuber yield was controlled by different grafting and cultivation approaches , and the correlation between tuber yield and pollen vigor was studied. Comparative transcriptomic analysis of pollen potential substrates for grafting-induced changes in potato scion fertility. Result: Grafting with the tomato rootstock effectively promoted the flower and fruit formation in the scion potato and improved its pollen viability by 15–20%. In addition, a significant negative correlation was observed between the potato tuber yield and pollen viability, suggesting a potential impact on the metabolic regulatory network related to tuber formation. Comparative transcriptomic analysis between the pollens from Q9 self-grafted plants and Q9-tomato grafting scion, 513 differentially expressed genes (DEGs) were identified. These DEGs were found to be related to gametophyte and pollen development, carbohydrate metabolism, and protein processing. Thus, these DEGs might be involved in improved fertility after reduced tuberization in plants subjected to heterologous grafting. Discussion: potato/tomato heterologous grafting significantly improved the pollen viability of scion potatoes and was associated with the absence of potato tubers. Heterologous grafting promotes the transcription of genes related to protein processing, carbohydrate metabolism, and pollen development in pollen cells, resulting in the production of fertile pollen. Our results provided initial clues to understanding the improvement of potato fertility using the heterologous grafting method, which might be a useful tool in assisted potato breeding